Factors influencing the choice of higher education institution and diploma programme among Universiti Teknologi MARA (UiTM) students / Mohammad Isa Mohamadin and Nor Hazizah Julaihi - Mohamadin, Mohammad Isa; Julaihi, Nor Hazizah (UiTM Press, 2023)
Education based on Science, Technology, Engineering and Mathematics (STEM) plays a pivotal role in providing technically skilled human resources for the development of the nation. However, in Malaysia, the number of students taking STEM-related programmes in higher education institutions (HEI) is still low. The actual factors behind such scenario are still unclear and need to be further investigated. With better understanding on the influential factors, the relevant authority can come up with appropriate strategies to increase students' enrolment in STEM-related programmes. Thus, this study is embarked to determine the factors that influence the students' choice of HEI and diploma programme at Universiti Teknologi MARA (UiTM). A quantitative approach was employed by disseminating a questionnaire to 779 diploma students from Semester 1 and Semester 2 of April - August 2022 session. The quantitative data analysis methods used in this study includes descriptive statistics.